A new species of the southern Central American genus Linoderus Sharp (Coleoptera: Staphylinidae: Staphylininae) with a revised key and an updated phylogeny - Chani-Posse, Mariana Raquel (Zootaxa, 2021)
Linoderus smetanai sp. nov. is described from Costa Rica. This is the third species in the southern Central American genus Linoderus of the subtribe Philonthina (tribe Staphylinini). The new species was included in a previous dataset of 52 morphological characters scored for the genus and representatives of its allied genera (Neopescolinus Chani-Posse, Paederomimus Sharp, Pescolinus Sharp) and its phylogenetic position analysed by Maximum Parsimony and Bayesian Inference. The analyses unambiguously placed L. smetanai within Linoderus in a sister-group relationship with L. alajuelensis Chani-Posse & Solodovnikov and L. gracilipes Sharp. A revised key to species and an updated phylogeny of Linoderus are also provided.